Accretion of gas onto nearby spiral galaxies - Fraternali, F; Binney, J (2008)
We present evidence for cosmological gas accretion onto spiral galaxies in the local universe. The accretion is seen through its effects on the dynamics of the extra-planar neutral gas. The accretion rates that we estimate for two nearby spiral galaxies are of the order of their star formation rates. Our model shows that most of the extra-planar gas is produced by supernova feedback (galactic fountain) and only 10-20 % comes from accretion. The accreting material must have low specific angular momentum about the disc's spin axis, although the magnitude of the specific angular-momentum vector can be higher. We also explore the effects of a hot corona on the dynamics of the extra-planar gas and find that it is unlikely to be responsible for the observed kinematical pattern and the source of accreted gas. However, the interaction with the fountain flow should profoundly affect the hydrodynamics of the corona.